Looking back from the periphery; Situating Indonesian provincial museums as cultural archives in the late-colonial to post-colonial era - Perkasa, Adrian; Arainikasih, Ajeng Ayu (Wacana, Journal of the Humanities of Indonesia, 2023)
Discussions on post-coloniality are often situated either in the centre of the colonizer or colonial metropole or the centre of the former colonized. The local perspective, especially in Indonesia, seems overlooked in existing literature, whereas it could be regarded as the cultural archive of the colonial era to post-independence Indonesia. Edward Said (1994) has said that cultural archives are a storehouse of a particular knowledge and structures of attitude and a reference to and structure of feelings. Gloria Wekker (2016) elaborates on the cultural archive; it has influenced historical cultural configurations as well as current dominant, cherished self-representations and culture. This paper examines the role of two provincial museums in Indonesia: Mpu Tantular Museum Surabaya and the Sonobudoyo Museum Yogyakarta, as cultural archives for each region. Since their foundation in the colonial era by the Europeans and local elite figures, these museums have seen many political changes. This paper delves into the archives and exhibitions of the museums to assess how they deal with their exhibition narratives as a colonial legacy, and to what extent these provincial museums have been involved in decolonization discourse. It proposes another way of looking at the post-colonial situation in Indonesian museums, not at the centre but more on the periphery.